Financial sector development and income inequality nexus in South Africa - Malatsi, Agnes Tlhalefang (Rhodes University, 2026)
This study investigates the relationship between financial sector development and income inequality in South Africa. The study explores financial depth and efficiency as facets of financial sector development. Despite having the most developed financial sector in Africa, South Africa has the highest income inequality in the world, with a Gini score of 0.63 since 2022 despite government interventions such as social grants and minimum wage policies intended to reduce income inequality. The country’s ongoing income inequality raises critical questions about the impact that the development of the financial sector may be exerting on this persistent inequality. The study utilizes annual time-series data from 1980 to 2020. The study applies the Autoregressive Distributed Lag (ARDL) model to examine both the short and long-run dynamics between financial development and income inequality, particularly focusing on the long-run dynamics. The ARDL model is best for this time-series analysis as it accepts variables of different integration of order. The analysis employs the Gini coefficient and the Palma ratio as complementary measures of inequality, and includes relevant macroeconomic control variables such as government expenditure, foreign direct investment (FDI), GDP per capita, inflation, and trade openness. Based on the key findings of the study, income inequality (proxied by the Gini coefficient) in South Africa can be reduced through the development of the financial sector (proxied by Public Debt Securities to GDP). In support of the Inequality-narrowing hypothesis, which posits that financial development reduces inequality by providing the marginalized population with better access to financial services, the study mainly found that in the long run, financial sector development reduces inequality through the facet of depth. Based on the findings of this study, relevant South African policymakers could promote financial inclusion initiatives, including expanding access to credit for low-income earners and small businesses. In addition, low-cost banking services or mobile banking platforms can also be implemented to increase credit penetration in underserved areas. This study contributes to the limited body of literature on the financial sector development and income inequality nexus in South Africa by incorporating both underexplored facets of financial development (financial efficiency) and complementary inequality metrics (Gini coefficient and Palma ratio).
Keywords: Uncatalogued